Estimates in household furnishings - Train, Doris M. (My University, 1906)
Introduction: The House Comfortable, for which this thesis contains an itemized account of furnishings, contains seven rooms: kitchen, dining room, two bed rooms, sewing room, living room, parlor and a reception hall. The allowance for equipping this home, to be occupied by a very small family is a thousand dollars; the income of the family is a moderate one; the house is situated in a small town and is without modern conveniences. The object of this thesis is to make an investigation of the actual cost of furnishing a house and as the idea in view is to determine the essential articles in equipping a home, this thesis deals only with the cost and quality of the article rather than with artistic arrangement as to color schemes, etc., of the articles previously purchased. To achieve the House Comfortable it is necessary to start with sound principles and to keep constantly in mind the ends for which a home is established. A home should yield rest, refreshment and inspiration to the members of the family; should be the place in which each member gathers renewed courage. It follows therefore that those parts which most affect the daily health and happiness of the household should be equipped first and most thoroughly, hence the kitchen is the first to be considered.
Citation: Train, Doris M. Estimates in household furnishings. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Home Economics; Home Furnishings; Furniture; Equipment; Theses; Manuscripts (documents)